2015
DOI: 10.1002/phar.1611
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes in Patients with Parkinson's Disease Treated with a Monoamine Oxidase Type‐B inhibitor: A Cross‐Sectional, Cohort Study

Abstract: Study ObjectiveTo evaluate the long‐term risk of developing cognitive symptoms (e.g., dementia, hallucinations), dyskinesia, falls, and freezing of gait (FoG) in patients with Parkinson's disease (PD) who received monoamine oxidase type B inhibitors (MAOB‐Is) compared with patients who had never received MAOB‐Is.DesignRetrospective, cross‐sectional, cohort study.SettingAcademic movement disorders clinic.PatientsOne hundred eighty‐one patients with idiopathic PD who were receiving MAOB‐I therapy on a long‐term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 18 publications
2
13
0
1
Order By: Relevance
“…These findings were in line with earlier work showing marginally faster gait speed in PD subjects on MAOB-I compared to placebo [82]. However, a more recent, retrospective study could not replicate a beneficial long-term effect of MAOB-I on FoG or fall risk [83]. In addition, clinical lore suggests that addition of a MAOB-I to a patient developing FoG does not reduce the symptom.…”
Section: Other Antiparkinsonian Drugssupporting
confidence: 88%
“…These findings were in line with earlier work showing marginally faster gait speed in PD subjects on MAOB-I compared to placebo [82]. However, a more recent, retrospective study could not replicate a beneficial long-term effect of MAOB-I on FoG or fall risk [83]. In addition, clinical lore suggests that addition of a MAOB-I to a patient developing FoG does not reduce the symptom.…”
Section: Other Antiparkinsonian Drugssupporting
confidence: 88%
“…For example, monoamine oxidase inhibitors (MAOI), which enhance dopamine function, have shown positive effects in patients with treatment-resistant depression (Fawcett et al, 2016 ). Monoamine oxidase type B (MAOB) inhibitors have elicited neuroprotective effects in preclinical models of PD and longer exposure to these inhibitors have been associated with less clinical decline in PD patients (Hauser et al, 2017 ) and reduced risk of dyskinesia (Dashtipour et al, 2015 ). Early treatment with rasagline, another MAOB inhibitor, resulted in improvement in UPDRS scores thus showing promise as a neuroprotective agent in PD patients (Olanow et al, 2009 ).…”
Section: Depression and Parkinson’s Diseasementioning
confidence: 99%
“…In 2009, the FDA expanded the indication for rasagiline from monotherapy and adjunct to levodopa to include adjunct to dopamine agonists. A recent cross-sectional cohort study reviewed the outcome of clinical MAO-B inhibitor investigation and demonstrated that MAO-B inhibitor therapy was associated with reduced risk of dyskinesia in patients with PD (Dashtipour et al, 2015). Currently, safinamide, approved in the EU, is waiting for regulatory approval as an add-on therapy to stable-dose levodopa, alone or in combination with other PD therapies in mid-to late-stage fluctuating PD patients (Deeks, 2015).…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%